Molecular detection of Anaplasmataceae agents in Dasyprocta azarae in northeastern Brazil - Braga, Maria do Socorro Costa de Oliveira; Pereira, José Gomes; Fernandes, Simone de Jesus [UNESP]; Marques, Ingrid Carolinne Lopes; de Jesus, Renata Passos; Ferreira, Gleycianny Santos; Xavier, Daniele Rosa; Benevenute, Jyan Lucas [UNESP]; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP] (FapUNIFESP (SciELO), 2018)
Recently, the importance of wild-living rodents for maintenance of pathogens of the family Anaplasmataceae in the environment was investigated. These mammals play a role as reservoirs for these pathogens and act as hosts for the immature stages of tick vectors. The aim of the present study was to investigate the prevalence of Ehrlichia sp. and Anaplasma sp. in 24 specimens of Azara’s agouti (Dasyprocta azarae) that had been trapped in the Itapiracó Environmental Reserve, in São Luís, Maranhão, northeastern Brazil, using molecular methods. Four animals (16.7%) were positive for Ehrlichia spp. in nested PCR assays based on the 16S rRNA gene. In a phylogenetic analysis based on the 16S rRNA gene, using the maximum likelihood method and the GTRGAMMA+I evolutionary model, Ehrlichia sp. genotypes detected in Azara’s agoutis were found to be closely related to E. canis and to genotypes relating to E. canis that had previously been detected in free-living animals in Brazil. The present work showed the first molecular detection of Ehrlichia sp. in Azara’s agoutis in Brazil.
Detecção molecular de agentes Anaplasmataceae em Dasyprocta azarae no nordeste do Brasil
Keywords: Azara’s agouti; Ehrlichia; Molecular characterization; Rodents